ECOLOGICAL DEGRADATION AND OLIGARCHIC NETWORKS IN INDONESIAN NOVELS - Dwi Budiyanto; Hartono, Hartono; Kusmarwanti, Kusmarwanti; Else Liliani (Universitas Negeri Yogyakarta, 2023)
The exploitation of nature has led to an ecological crisis that is not only a local threat but has expanded as a global catastrophe. Literature represents the degradation of nature as well as the power relations among the oligarchic networks operating around it to build ecological awareness for the community. This descriptive-qualitative research design aims to describe the form of ecological degradation and the role of oligarchic power networks that appear in Indonesian novels. The data sources were purposively selected from Indonesian novels with ecoliteracy insights, including Api Awan Asap by Korrie Layun Rampan (2015), Jemangilak Tak Pernah Menangis by Martin Aleida (2004), and Kelomang by Qizink La Aziva (2016). In addition, data sources related to nature and the environment depicted in the three novels were also used. The data were obtained using reading and note-taking techniques. Furthermore, it was analyzed qualitatively using the perspective of literary ecology through categorization, tabulation, and inference. The results of this study concluded that (1) the forms of ecological damage presented in Indonesian novels are (a) river sedimentation and pollution, (b) coastal abrasion, and (c) forest fires. (2) Forms of natural damage occur due to exploitation actions carried out by oligarchic networks supported by government regulations and licenses. The study of ecological literary works builds awareness of the process of ecological degradation and the perpetrators of destruction that form a systemic network.